2000
DOI: 10.1108/02635570010304806
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Internet shopping: the role of consumer innovativeness

Abstract: The projected sales potential for Internet commerce indicates that businesses must understand those consumer characteristics that will influence consumer adoption of this medium for shopping. An empirical study conducted here (n = 403) investigates the extent to which open‐processing (more general innovativeness) and domain‐specific innovativeness explain the conditions under which consumers move from general Internet usage to a product purchase via the Internet. The results of our study find that generally hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(69 citation statements)
references
References 17 publications
3
60
1
5
Order By: Relevance
“…Chao et al (2012) showed that the positive and proper relation exists between the domain-specific innovativeness and innovative behavior of adoption new product which stated that the consumers, who have more powerful relation with specific group of products, adopt the product sooner that the others. This study verifies the previous researchers such as (Citrin, Sprott, Silverman, & Stem, 2000) and (Goldsmith, Freiden, & Eastman, 1995 Chao et al (2012) stated that the domain-specific innovativeness can better predict the adoption and shopping of new product behavior that the cognitive innovativeness. Their results show that a weak direct relation exists between the cognitive innovativeness and adoption of new products.…”
Section: The Relation Between the Various Levels Of Consumer Innovatisupporting
confidence: 70%
See 1 more Smart Citation
“…Chao et al (2012) showed that the positive and proper relation exists between the domain-specific innovativeness and innovative behavior of adoption new product which stated that the consumers, who have more powerful relation with specific group of products, adopt the product sooner that the others. This study verifies the previous researchers such as (Citrin, Sprott, Silverman, & Stem, 2000) and (Goldsmith, Freiden, & Eastman, 1995 Chao et al (2012) stated that the domain-specific innovativeness can better predict the adoption and shopping of new product behavior that the cognitive innovativeness. Their results show that a weak direct relation exists between the cognitive innovativeness and adoption of new products.…”
Section: The Relation Between the Various Levels Of Consumer Innovatisupporting
confidence: 70%
“…Christia (2014) showed that the relation between the cognitive innovativeness and domain-specific innovativeness is more than the relation between the cognitive innovativeness and the probability to adopt new product. Citrin et al (2000) show that domain-specific innovativeness has positive and significant impact on emergence of innovative behavior of new product adoption, also domain-specific innovativeness has the facilitator and resonator role in the relation between the cognitive innovativeness and adoption of the new products on the internet. Wang & Shih (2015) showed in their research that with reference to the impact of consumer innovativeness on the shopping of new computer games online, cognitive innovativeness and domain-specific innovativeness have direct effect on shopping of the new games online, also the Variety Seeking Behavior (domain-specific innovativeness) has significant impact as the mediator between the cognitive innovativeness and the behavior of new product adoption and causes that the prediction power of adoption behavior increases dramatically in the cognitive consumer.…”
Section: The Relation Between the Various Levels Of Consumer Innovatimentioning
confidence: 99%
“…Based on this theory, perceived self-efficacy towards certain behaviors is expected to influence individuals' responses to their surrounding environments. Drawing upon the concept of self-efficacy, numerous studies have shown that prior relevant product knowledge and experience is positively related to the adoption of new technologies (Citrin, Sprott, Silverman, & Stem, 2000;Kulviwat, Thaku, & Guo, 2006;Lian & Lin, 2008;O'Cass & Fenech, 2003). For example, a consumer who is familiar with and capable of making a purchase via the Internet is more likely to adopt the Internet as an alternative shopping channel (Kulviwat et al, 2006).…”
Section: Online Shopping Frequency and Device Usagementioning
confidence: 99%
“…For example, 6-items measure Fashion innovativeness construct is adopted from the study of Park et al (2007). Six items measure Consumer innovativeness variable is adopted from the studies of (Goldsmith & Hofacker, 1991;Citrin et al, 2000;Park et al, 2007;Aldás-Manzano et al, 2009). Five items measure the Fashion involvement construct, is derived from the studies of (Belton & Clinton, 2007;Cardoso et al, 2010).…”
Section: Instrument and Measuresmentioning
confidence: 99%